의약품 지출 비용에 미치는 영향 요인 - 한국의료패널자료를 활용하여 - 김윤정; 황병덕; Kim, Yun-Jeong; Hwang, Byung-Deog (한국콘텐츠학회 논문지, 18(4), 2018)
This study used raw data from the Korea Medical Panel Survey for 2014 to analyze the factors affecting the cost of medicine expenditure. A total of 3,107 people with medical expenses were selected for the final analysis. Analysis methods were frequency analysis, crossover analysis, regression analysis and t-test. The significance level of all tests was p = .05. The prescription cost was 72.4%, the minimum cost was 84 won, the maximum cost was 270,653 won, and the highest amount was 'over 3,000 won~less than 10,000 won' (31.7%). The general pharmaceuticals cost was 81.8%, the minimum cost was 800 won, the maximum cost was 2,718,000 won, and the highest amount was 'less than 20,000 won' (31.4%). The herbal medicine cost was 9.4%, the minimum cost was 4,000 won, the maximum cost was 2,700,000 won, and the highest amount was 'over 100,000 won' (37.8%). The medicines expenditure was the maximum cost was 2,760,093 won, and the highest amount was 'over 100,000 won' (27.0%). Factors affecting medicine expenditure were gender, marital status, income quintile, easement, and subjective health status. 본 연구는 의약품 지출 비용에 미치는 요인을 파악하기 위하여 한국의료패널조사의 2014년 원자료를 분석자료로 이용하여, 의약품 지출 비용이 있는 자 3,107명을 최종 분석 대상으로 하였다. 분석은 빈도분석, 교차분석, 회귀분석 및 t-test를 실시하였고, 모든 검증은 p=.05를 유의수준으로 하였다. 처방전 비용은 72.4%가 지출 경험이 있었고, 최소 비용은 84원, 최대 비용은 270,653원 이었고, '3천원 이상~1만원 이하'가 31.7%로 가장 많았다. 일반의약품 비용은은 81.8%가 지출 경험이 있었고, 최소 비용은 800원, 최대 비용은 2,718,000원 이었고, '2만원 이하'가 31.4%로 가장 많았다. 한약 및 첩약 비용은 9.4%가 지출 경험이 있었고, 최소 비용은 4,000원, 최대 비용은 2,700,000원 이었고, '10만원 초과'가 37.8%로 가장 많았다. 의약품 지출 총 비용은 최소 비용은 84원, 최대 비용은 2,760,093원 이었고, '10만원 초과'가 27.0%로 가장 많았다. 의약품 지출비용에 미치는 요인은 성별, 혼인상태, 소득분위, 지역권, 주관적 건강상태 이었다.